Melatonin Plays a Critical Protective Role in Nicotine-Related Abdominal Aortic Aneurysm - Duan, Liren; Li, Shenli; Wang, Lei; Jing, Yuchen; Li, Guangxin; Sun, Yaodong; Sun, Weifeng; Li, Yalun; Zhao, Lin; Xin, Shijie (Frontiers in Physiology, 2020)
Aim: Smoking is a major risk factor for abdominal aortic aneurysm (AAA). Among the components of smoke, nicotine is known to exert proatherosclerotic, prothrombotic and proangiogenic effects on the vascular smooth cells. The current study was designed to investigate the mechanisms by which nicotine induces the vascular wall dysfunction and further to examine whether melatonin could protect against nicotine-related AAA. Methods: In this study, an enzyme-linked immunosorbent assay (ELISA) was used to measure melatonin and TNF-α levels and total antioxidant status (TAS) in AAA patients and control individuals. We established a nicotine-related AAA model and explored the mechanism underlying the therapeutic effects of melatonin. Tissue histopathology was used to assess vascular function. Western blotting (WB) and immunofluorescence were used to detect protein expression. Results: We demonstrated melatonin insufficiency in serum from AAA patients, especially smokers. Moreover, the melatonin level was positively correlated with antioxidant capacity. In in vivo models, nicotine accelerated AAA expansion and destroyed vascular structure. Further study showed that OPN, LC3II, p62, MMP-2, MMP-9, NF-κB p65, TNF-α, phosphorylated AKT and phosphorylated mTOR levels were increased in vivo after nicotine treatment, while SM22α and α-SMA levels were reduced. Additionally, melatonin attenuated the effects of nicotine on AAA and reversed the protein expression changes. Moreover, melatonin lost its protective effects following Bafilomycin A1 inhibition of autophagy. Conclusions: Our data suggest that melatonin exerts a beneficial effect on rats with nicotine-related AAA by downregulating the AKT-mTOR signalling pathway, improving autophagic dysfunction, and restoring the vascular smooth muscle cell (VSMC) phenotype.